2010
DOI: 10.1121/1.3436522
|View full text |Cite|
|
Sign up to set email alerts
|

Speech reception by listeners with real and simulated hearing impairment: Effects of continuous and interrupted noise

Abstract: The effects of audibility and age on masking for sentences in continuous and interrupted noise were examined in listeners with real and simulated hearing loss. The absolute thresholds of each of ten listeners with sensorineural hearing loss were simulated in normal-hearing listeners through a combination of spectrally-shaped threshold noise and multi-band expansion for octave bands with center frequencies from 0.25-8 kHz. Each individual hearing loss was simulated in two groups of three normal-hearing listener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
76
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 47 publications
10
76
1
1
Order By: Relevance
“…One explanation derives from the effects of reduced audibility in HI listeners. As shown by Desloge et al (2010), it is as if the HI were NH listeners who experienced a background noise that raised their thresholds to those of the HI and consequently prevented them from "listening in the valleys" where the interference is relatively weak. The reduction in cochlear compression and decreased frequency selectivity that accompany sensorineural loss are another possible source of decreased MR (Moore et al, 1999;Oxenham and Kreft, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation derives from the effects of reduced audibility in HI listeners. As shown by Desloge et al (2010), it is as if the HI were NH listeners who experienced a background noise that raised their thresholds to those of the HI and consequently prevented them from "listening in the valleys" where the interference is relatively weak. The reduction in cochlear compression and decreased frequency selectivity that accompany sensorineural loss are another possible source of decreased MR (Moore et al, 1999;Oxenham and Kreft, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding speech in noise, restaurants, or group situations continues to be problematic for hearing-aid users, in spite of research efforts. When the interference is temporally fluctuating, most normal-hearing (NH) individuals are able to achieve substantial gains in intelligibility while most HI listeners do not (e.g., Desloge et al, 2010). Recently, a number of investigators (e.g., Lorenzi et al, 2006Lorenzi et al, , 2009Hopkins and Moore, 2007;Hopkins et al, 2008) have shown that this may result from an inability of HI listeners to process the temporal fine structure (TFS), as opposed to the temporal envelopes (ENVs), of speech as well as NH listeners.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (e.g., Bernstein and Grant, 2009;Oxenham and Simonson, 2009;Desloge et al, 2010) has shown a tendency for an increase in MR as SNR decreases and for MR to disappear at SNR >0 dB. To examine the role of the specific SNRs employed here on MR for the different types of speech processing, performance was measured on two of the HI listeners (HI-3 and HI-5) at several additional values of SNR.…”
Section: Discussionmentioning
confidence: 99%
“…In continuous noise, HI listeners typically require a higher speech-to-noise ratio (SNR) to achieve the same level of performance as NH listeners (e.g., Festen and Plomp, 1990). Furthermore, HI listeners do not show as great an improvement as NH listeners in fluctuating compared to continuous noise (Festen and Plomp, 1990;Moore et al, 1999;Bernstein and Grant, 2009;Desloge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation